2022
DOI: 10.21203/rs.3.rs-1414181/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significant Mechanism of Lorentz Force in Energy Transfer Phenomena Involving Viscous Dissipation via Numerical Strategy

Abstract: Transport of heat in two dimensional fluid model is reported in this exploration. The flow is assumed to be two dimensional and incompressible. The involvement of variable magnetic field is considered to retard the flow to study its characteristics. The flow model is developed in Cartesian coordinates system. The transport of heat is considered under the inspiration of viscous dissipation and Joule heating effects with thermal and velocity slips at boundary. Theory of boundary layer is considered in order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Rostami et al (2022) studied the hydro-thermal analysis. Moreover, the studies reported by, Hosseinzadeh et al (2021a); Hosseinzadeh et al (2021b);Sohail et al (2022a);Sohail et al (2022b); Hou et al (2022) are prepared to notice the comportment of numerous involved parameters on momentum and thermal transport. There are no studies in the existing literature that involve synovial fluid and consider the two different nanofluid models over a two-dimensional stretched surface through use of different shaped nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Rostami et al (2022) studied the hydro-thermal analysis. Moreover, the studies reported by, Hosseinzadeh et al (2021a); Hosseinzadeh et al (2021b);Sohail et al (2022a);Sohail et al (2022b); Hou et al (2022) are prepared to notice the comportment of numerous involved parameters on momentum and thermal transport. There are no studies in the existing literature that involve synovial fluid and consider the two different nanofluid models over a two-dimensional stretched surface through use of different shaped nanoparticles.…”
Section: Introductionmentioning
confidence: 99%